The heterogeneous earnings impact of job loss across workers, establishments, and markets - Susan Athey; Lisa Simon; Oskar Nordström Skans; Johan Vikström; Yaroslav Yakymovych (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2024)
Using generalized random forests and rich Swedish administrative data, we show that the earnings effects of job displacement due to establishment closures are highly heterogeneous. We find as much heterogeneity within as across closing establishments, and within as across worker types defined by age and schooling. We display the potential of market-based policy interventions by showing that much of the heterogeneity across establishments is shared within markets. Several results suggest that the effect heterogeneity disfavors already vulnerable workers. Thus, targeted policy interventions may be justified to a larger extent than suggested by estimated average earnings effects.
Keywords: J65; J21; J31; C45; 330; Plant closures; heterogeneous effects; GRF